PANGERAN ASIR SANG PENGUASA KAWEDANAN RUPIT RAWAS (TINJAUAN HISTORIS KEPEMIMPINAN POLITIK PANGERAAN ASIR TAHUN 1922-1942) - Yadri Irwansyah (Diakronika, 2018)
The study of this study discusses the historical aspects of the political leadership of Prince Asir, ruler of KawedananRupitRawas (1922-1942). RupedRawasKawedanan was a Dutch territory after the fall of the Palembang Sultanate. KawedananRupitRawas was led by Prince Asir as local leader of RupitRawas over the mandate given by the Dutch colonial government. This study uses the History method to explore the Local History of the Palembang Sultanate in the past. The stages of research begin with heuristics, source criticism, interpretation, and historiography. The research findings show that RupitRawasKawedanan at that time had a fertile area that produced natural resources, such as rubber, fruits and others. This area is drained by Rawasriver which then encourages the emergence of trade activities. Prince Asir is a charismatic leader who leads RupitRawas. He is a Dutch colonial leader who is considered capable, intelligent and accomplished and is considered capable of maintaining a commitment to the Netherlands. He was known as a wise leader and left many historical traces at RupitRawasKawedanan. During the struggle for Indonesian independence, Prince Asir was very instrumental in facilitating the Indonesian nation's struggle in Sumatra against the Dutch.